Belief in a just world lowers bribery intention. Issue 1 (14th July 2015) - Bai, Bao‐yu; Liu, Xiao‐xiao; Kou, Yu
Abstract : Corruption is rampant around the world and can be detrimental to social justice. We aim to understand whether and how belief in a just world to self (BJW‐self) influences individuals' intentions to become involved in bribery. We measured bribery intention using hypothetical scenarios. In Study 1 and Study 2, we consistently found that BJW‐self negatively predicted bribery intention, and this pattern was mediated by perceived punishment of getting involved in bribery. We further demonstrated the causal effect of BJW‐self on bribery intention in an experiment (Study 3). These results indicate that BJW as one lay belief can be important in suppressing people's bribery intention, and perceived punishment mediates the effect of BJW on rule‐breaking behaviours. Implications for anti‐corruption policies and future research are also discussed.